SIMILARITIES AND DIFFERENCES IN PREPOSITIONS AND ENDINGS OF THE RUSSIAN AND UZBEK LANGUAGES (ON THE EXAMPLE OF USE WITH NOUNS) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is devoted to the problems of the modern Russian language.